2022
DOI: 10.1155/2022/5511555
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Risk Perceptions of Chronic Kidney Disease Risk Factors among Women of Childbearing Age in Lagos State, Nigeria: From a Health Demography Approach

Abstract: Background. Kidney disease (KD), also known as chronic kidney disease (CKD), is a long-term underrecognized public health concern and one of the eight leading causes of death in women. Despite that, little is known about women’s knowledge, perceived risk, and perceptions of CKD risk factors. In this study, we assessed knowledge, perceived risk, and perceptions of CKD risk factors among women of childbearing age in Lagos State, Nigeria. Methods. Administering a pretested and structured questionnaire among 825 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…These protective effects may be because coffee contains antioxidant and anti-inflammatory components ( 31 ), and alcohol and tea contain polyphenols that can reduce reactive oxygen species and anti-inflammatory components ( 32 , 33 ). We also found that frequent analgesics use, hypertension, and diabetes were significantly associated with CKD, and these results were similar to other studies ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 92%
“…These protective effects may be because coffee contains antioxidant and anti-inflammatory components ( 31 ), and alcohol and tea contain polyphenols that can reduce reactive oxygen species and anti-inflammatory components ( 32 , 33 ). We also found that frequent analgesics use, hypertension, and diabetes were significantly associated with CKD, and these results were similar to other studies ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 92%
“…Healthcare providers should prioritize regular screening for CKD risk factors and symptoms during routine checkups. [ 42 , 43 ] This proactive approach can lead to early diagnosis and intervention, potentially halting disease progression. Furthermore, there a clear need for improved public awareness and knowledge about CKD.…”
Section: Discussionmentioning
confidence: 99%
“…This study finding is not consistent with previous studies, as few studies have indicated that educated grandparents experience health challenges owing to self-neglect. Recent studies have evidently stated that self-neglect is linked with adverse outcomes concerned with older adults' physical [4,6] and psychological well-being [6,7], loss of dignity and self-esteem [7,38], illness [38,39], death [21,68] and healthcare utilisation [72,73].…”
Section: Discussionmentioning
confidence: 99%